Estimation of the antiviral activity of ribamidil within the model of mixed adeno-herpetic infection - Biliavska, L. O.; Nesterova, N.V.; Povnitsa, O.Yu.; Voychuk, S. I.; Bobko, T.N. (Reports of the National Academy of Sciences of Ukraine, 2014)
A model of mixed adeno-herpetic infection of cells MDBK is developed, and features of the reproduction of viruses are described. The simultaneous infection of cells caused the inhibition of reproduction of both viruses. The amplification of HadV-5 reproduction and the inhibition of HSV-1/US reproduction in the case where cells were superinfected by herpesvirus are shown. The efficiency of ribamidil has been studied under conditions of mixed infection of cells. 100% inhibition of the adenovirus reproduction by ribamidil under the conditions of mono- and mixed infections is detected. Under the conditions of mixed infection, the efficiency of ribamidil against HSV-1 decreases.